Natto extract, a Japanese fermented soybean food, directly inhibits viral infections including SARS-CoV-2 in vitro - Oba, Mami; Rongduo, Wen; Saito, Akatsuki; Okabayashi, Tamaki; Yokota, Tomoko; Yasuoka, Junko; Sato, Yoko; Nishifuji, Koji; Wake, Hitoshi; Nibu, Yutaka; Mizutani, Tetsuya (Biochemical and biophysical research communications, 2021)
Natto, a traditional Japanese fermented soybean food, is well known to be nutritious and beneficial for health. In this study, we examined whether natto impairs infection by viruses, such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) as well as bovine herpesvirus 1 (BHV-1). Interestingly, our results show that both SARS-CoV-2 and BHV-1 treated with a natto extract were fully inhibited infection to the cells. We also found that the glycoprotein D of BHV-1 was shown to be degraded by Western blot analysis and that a recombinant SARS-CoV-2 receptor-binding domain (RBD) was proteolytically degraded when incubated with the natto extract. In addition, RBD protein carrying a point mutation (UK variant N501Y) was also degraded by the natto extract. When the natto extract was heated at 100 °C for 10 min, the ability of both SARS-CoV-2 and BHV-1 to infect to the cells was restored. Consistent with the results of the heat inactivation, a serine protease inhibitor inhibited anti-BHV-1 activity caused by the natto extract. Thus, our findings provide the first evidence that the natto extract contains a protease(s) that inhibits viral infection through the proteolysis of the viral proteins. •Natto extract, which is a traditional Japanese fermented soybean food, fully inhibited infection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and bovine herpesvirus 1 (BHV-1) to the cells.•The UK variant of spike protein (receptor binding domain; RBD) of SARS-CoV-2 and Glycoprotein D of BHV-1 were proteolytically degraded by the natto extract.•A serine-protease(s) in the natto extract is worth to be further investigated as antiviral drug(s).